(3GdeQLY aj hXjaI GdGMJjGLGJ hEOGQI GdCfTWI GddhLSJjI aj GdefXeGJ GdeYGUQI (B:s (3eONd GSJQGJjLj JWHjbj dJMbjb GdejRI GdJfGaSjI ef NdGd CYeGd GdTQGA hGdJNRjf (B/s - (3HcQ, eUWai eMehOs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2004)
(3GdEWGQ GdYGe dhXjaI GdGMJjGLGJ hEOGQI GdCfTWI GddhLjSJjI,GdHfGA GdJfXjej hGdfXGe GdEOGQj ddCfTWI GddhLjSJjI hEOGQI GdGMJjGLGJ,JNWjW GdEeOGOGJ GddhLjSJjI hJhajQ GdGMJjGLGJ,GdfeGPL GdQFjSjI dYedjI GdJNWjW GdGSJQGJjLj ddCfTWI GddhLjSJjI hEOGQI hXjaI GdGMJjGLGJ,JMOjO GdehGUaGJ hLhOI bQGQ GdTQGA,JMOjO GdcejI GdefGSHI hLhOI bQGQ GdTQGA,JMOjO GdSYQ GdefGSH hLhOI bQGQ GdTQGA,JMOjO GdhbJ GdefGSH hLhOI bQGQ GdTQGA,JMOjO eUOQ GdJhQjO hLhOI bQGQ GdTQGA,eQGMd hELQGAGJ COGA GdCfTWI GddhLjSJjI hJhajQ GdGMJjGLGJ,OhQ GdJaGhV aj COGA GdCfTWI GddhLjSJjI hJhajQ GdGMJjGLGJ,eJGHYI GdJhQjOGJ hJbhje COGA hXjaI GdGMJjGLGJ,caGAI GdCfTWI GddhLjSJjI hLhOI CYeGd GdeNGRf hGdeSJhOYGJ,eJGHYI hJbhje CYeGd GdeSJhOYGJ hGdeNGRfs
(3GdeQGLY U(B.550s
Keywords: (3GOGQI GdeNGRfs; (3GdHjYs; (3GdTQGAs